Development and validation method for simultaneous quantification of neomycin and polymyxin B by HPLC-ELSD and comparison with microbiological method - Henny Setiawati, Harmita Harmita, Herman Suryadi (Journal of Applied Pharmaceutical Science, 2020)
The aim of this study is to develop the first simultaneous method for quantification of neomycin and polymyxin B in the presence of dexamethasone using High Performance Liquid Chromatography (HPLC) with an Evaporative Light Scattering Detector (ELSD). The analysis was performed using a phenyl Waters X Bridge column, an evaporation temperature of 50oC, and a nitrogen pressure of 320 kPa. The mobile phase consists of a combination of methanol and trichloroacetate acid (40 mM, pH 1.70–1.80) in gradient mode, flow rate at 1.0 ml/minute, detector gain of 6, and analysis time of 35 minutes. The linearity was achieved with a concentration of 100–500 μg/ml (r = 0.99955) for neomycin and concentration of 30–100 μg/ml (r = 0.99703) for polymyxin B. Recovery results were obtained between 99.150% and 104.773% for neomycin and 96.538% and 105.139% for polymyxin B. The analysis sample from the market was found to be 102.27% for neomycin and 100.79% for polymyxin B. The result was compared to the standard microbiological method. Based on the T-test results of two samples with a 95% confidence level (α = 0.05), it was concluded that there was no significant difference between HPLC-ELSD and microbiological methods for determining neomycin and polymyxin B. The HPLC-ELSD method has a potential for routine analysis due to advantages in terms of increasing precision, accuracy, and shorter testing time.
Keywords: Antibiotics, evaporative light scattering detector, neomycin, polymyxin B.